Accumulated phosphatidylcholine (16:0/16:1) in human colorectal cancer; possible involvement of LPCAT4. Issue 10 (30th July 2013) - Kurabe, Nobuya; Hayasaka, Takahiro; Ogawa, Mikako; Masaki, Noritaka; Ide, Yoshimi; Waki, Michihiko; Nakamura, Toshio; Kurachi, Kiyotaka; Kahyo, Tomoaki; Shinmura, Kazuya; Midorikawa, Yutaka; Sugiyama, Yasuyuki; et al.
Abstract : The identification of cancer biomarkers is critical for target‐linked cancer therapy. The overall level of phosphatidylcholine (PC) is elevated in colorectal cancer (CRC). To investigate which species of PC is overexpressed in colorectal cancer, an imaging mass spectrometry was performed using a panel of non‐neoplastic mucosal and CRC tissues. In the present study, we identified a novel biomarker, PC(16:0/16:1), in CRC using imaging mass spectrometry. Specifically, elevated levels of PC(16:0/16:1) expression were observed in the more advanced stage of CRC. Our data further showed that PC(16:0/16:1) was specifically localized in the cancer region when examined using imaging mass spectrometry. Notably, because the ratio of PC(16:0/16:1) to lyso‐PC(16:0) was higher in CRC, we postulated that lyso‐PC acyltransferase (LPCAT) activity is elevated in CRC. In an in vitro analysis, we showed that LPCAT4 is involved in the deregulation of PC(16:0/16:1) in CRC. In an immunohistochemical analysis, LPCAT4 was shown to be overexpressed in CRC. These data indicate the potential usefulness of PC(16:0/16:1) for the clinical diagnosis of CRC and implicate LPCAT4 in the elevated expression of PC(16:0/16:1) in CRC.